2005
DOI: 10.1002/gepi.20114
|View full text |Cite
|
Sign up to set email alerts
|

Case-control analyses: Geneopardy!

Abstract: The case-control analyses group focused on a diverse set of questions, including study design, power, and analysis of case-control studies. Papers on study design examined various case-selection strategies, as well as ways to combine information from family- and population-based case-control data. The power of various approaches to case-control analyses was compared in several papers, while two papers chose to apply specific methods to analyzing the data. Two groups examined haplotype-related issues, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This problem is well known since the early days of genetics [6] , but, nonetheless, has been largely ignored in genetic epidemiological research. The revived interest in the case-control study design using genetic markers has stirred a recent debate about the relevance of confounding by population substructure and admixture [7][8][9][10] with lack of empirical evidence, especially when authors chose models with unrealistically differential prevalences leading to large effects [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…This problem is well known since the early days of genetics [6] , but, nonetheless, has been largely ignored in genetic epidemiological research. The revived interest in the case-control study design using genetic markers has stirred a recent debate about the relevance of confounding by population substructure and admixture [7][8][9][10] with lack of empirical evidence, especially when authors chose models with unrealistically differential prevalences leading to large effects [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Here, haplotypes were reconstructed using a maximum likelihood method, and the most likely pair of haplotypes for each individual was used for the analysis. For further discussion about the influence of the uncertainty of haplotype reconstruction, see Jorgenson et al [2005]. In contrast to Beckmann et al [2005a], Humphreys and Iles [2005] found statistical interaction between two genes only for singlelocus approaches, and not for multilocus genotype-or haplotype-based approaches.…”
Section: Haplotype Vs Genotype Approaches To Association Analysismentioning
confidence: 92%
“…Computations that weigh haplotype probabilities, rather than rely on the single most probable haplotype, become more important as SNP numbers increase. (See also the summary papers by Jorgenson et al [2005] and Beckman et al [2005] for further discussion of this point. )…”
Section: Additional Implications Of Ld and Other Marker Characteristicsmentioning
confidence: 93%